Analisis Determinan Struktur Modal pada Bank Perkreditan Rakyat Se-Eks Karisidenan Pekalongan Tahun 2017-2020 - Utami, Yuni; Berliana, Lusy Fina (Konsentrasi: Jurnal Manajemen dan Bisnis, 2022)
This study attempts to analyze and get the proof empirical influence liquidity, the structure of assets, tax and profitability to capital structure in public credit bank ex pekalongan residency in 2017-2020. This research was conducted at were all public credit bank ex pekalongan residency registered in authority financial services in 2017-2020. The sampling technique was carried out by purposive sampling method. The data analysis technique used is a descriptive technique with a quantitative approach using descriptive statistical tests, classic assumption tests, multiple linear regression analysis, t statistical tests, statistical tests f and coefficient of determination. This research result indicates that liquidity and profitability is the negative to structure capital in public credit bank ex pekalongan residency in 2017-2020. While structure of assets and tax will not affect the capital in public credit bank ex pekalongan residency in 2017-2020.